Vojislav Radovanović as an Ethnologist - Prelić (Serbia), Mladena (Bulletin of the Institute of Ethnography SASA, 2018)
Vojislav S. Radovanović (January 27th 1894, Pavlica/Raška – April 26th 1957, Belgrade), was a geographer–geomorphologist by formal education, but in the course of his academic career he also researched in the area of anthropogeography, ethnology and history. He was a student and assistant of Jovan Cvijić; professor of universities in Zagreb, Skopje and Belgrade; corresponding member of the Serbian Academy of Sciences (SAS) since 1940. He was one of the initiators of the establishment of the Institute of Ethnography SAS(A), and its first director (1947−1957). Contribution to ethnology by Vojislav Radovanović is somewhat overshadowed by his results in anthropogeography and geography. In this paper ethnological aspects of his work will be discussed. Key words: Vojislav S. Radovanović, history of ethnology in Serbia, anthropogeographic research, Macedonia